Child stunting in households with double burden of malnutrition: applications of behavioral epidemiology - Mahmudiono, Trias (Kansas State University, 2016)
Child stunting refers to a condition where the child is relatively shorter in height, in comparison to their age group. Child stunting is a public health nutrition problem that hinders the development of future generations, not only physiologically but also potentially deprives their cognitive function and productivity. The demographic transition, conjoined with the epidemiological and nutrition transitions, has resulted in the coexistence of an over- and under-nutrition problem known as double burden of malnutrition, and child stunting has been a persistent part of the problem. In 2014, the World Health Organization (WHO) reported that one-fourth of the children in the developing countries have been suffering from child stunting. The objective of this research was to apply the behavioral epidemiology approach to tackle child stunting in households with double burden of malnutrition. It was hypothesized that unlike any other households with problem of child stunting, households with double burden of malnutrition possess some degree of capacity that, with proper support and direction, might enable them to help themselves reduce or prevent this nutrition-related debacle. Results from a secondary data analysis revealed that child stunting was associated with lower dietary diversity as an indication of poor food choice in the household, related to children’s nutrient requirements. Another cross-sectional study in this dissertation was conducted in an urban setting in Indonesia, and found that households with child stunting alone was associated with extreme food insecurity, while households with double burden of malnutrition ─ in the form of stunted child and overweight/obese mother (SCOWT) ─ was associated with even a mild degree of food insecurity. These results support our hypothesis that households with double burden of malnutrition lack the capacity to direct their resources properly to prevent child stunting. Most notably, we expected that the role of the mothers to manage healthy food choices through indirect measure of dietary diversity, availability and distribution within the household was lacking. In order to equip mothers with necessary components to be able to overcome these problems, we conducted a behaviorally based intervention that targeted mothers in the households experiencing the problem of double burden of malnutrition. The intervention provided the potential to achieve participant self-administered goal setting to improve diet, as well as child feeding behavior, by means of improved self-efficacy, nutrition literacy and dietary diversity. Maternal self-efficacy may be potentially enhanced by vicarious experience and active mastery experience gained during 6 sessions of behavioral intervention and verbal motivation by community health workers during 6 additional home visits. These studies, collectively comprising the present dissertation, present a message for policy makers in developing countries: nutrition literacy and behaviors for choosing healthy foods are lacking in mothers that affect both maternal and child food intake, but efforts such as improving vicarious and mastery experience on child feeding practices and healthy food choices can boost mother’s self-efficacy to engage in appropriate behaviors and improve their child’s nutrition.
Keywords: Double burden of malnutrition; Child stunting; Behavioral epidemiology; Nutrition education; Public health nutrition; Maternal obesity